Measuring the impact of special collections and archives in the digital age: opportunities and challenges - Kamposiori, Christina (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
This paper is based on the outcome of a recent Research Libraries UK (RLUK) project that aimed to explore and understand the approaches employed by RLUK members for capturing and measuring the impact of activities based on special collections and archives. In today’s constantly evolving information and scholarly environment, educational and cultural institutions, such as research libraries, are faced with a pressing demand to assess the value of their services and evidence their impact. As part of our goal to develop a better understanding of how research libraries respond to this demand, we collected and analysed case-study and survey data from across the RLUK membership that show the practices and methods of research libraries for increasing and assessing the impact of their collections and related services. As our results showed, research libraries increasingly employ audience-focused strategies and take advantage of the new possibilities offered by the digital age to enhance access to collections, reach a range of audience groups and achieve greater impact. However, a number of issues, such as the lack of structured methodologies to capture and evaluate the full reach of digital collections and resources or the long-term impact of collections, can make the process of measuring and evidencing value a challenging task for institutions. In this paper, we will present some of the key findings showing the pathways to impact followed by special collection and archive professionals in the UK and Ireland and reflect on the opportunities and challenges that the digital era presents for increasing and measuring this impact.